PENINGKATAN MUTU LAYANAN PENDIDIKAN MELALUI OPTIMALISASI PERAN KOMITE MADRASAH - wida farwati, Wiwik (Lembaga Pendidikan Ma'arif Nahdlatul Ulama, Kabupaten Malang, Indonesia, 2024)
Community involvement in the education sector is facilitated through the Madrasah Committee organization established by each educational institution. This organization aims to ensure that community aspirations and initiatives are channeled, as well as to create responsibility, community participation, and a transparent, accountable and democratic atmosphere in the implementation of education. To ensure that this goal does not just become a slogan, it is necessary to optimize the role of the Madrasah Committee so that it can make a real contribution to education and improve the quality of education.